The Relationship between Mortality of Lung Transplant Recipients and Serum Cyclosporine Levels: Joint Modeling of Time-to-Event Data and Longitudinal Data - Hosseini-Baharanchi, F. S. (Int J Organ Transplant Med, 2017)
BACKGROUND: Lung transplantation (LTx) is a well-accepted treatment that can prolong survival of patients with advanced lung disease. OBJECTIVE: To evaluate the association between serum cyclosporine level (SCL) pattern and mortality of LTx recipients. METHODS: This retrospective cohort study included 1019 observations on 38 patients who underwent LTx in Masih Daneshvari Hospital from 2000 to 2013. The analysis applied a joint model with shared random effects. RESULTS: The mean±SD age of the recipients was 36±14.5 years. The findings indicated that sex, age, body mass index (BMI), the underlying disease, and cytomegalovirus infection were not associated with mortality. The mortality risk for the recipients with acute rejection (AR) history was 1.54 times that of the recipients who had none (95% CI: 1.08–2.19). The association parameter in the joint model (α = 0.8) showed that higher SCL was associated with lower mortality risk (95% CI: 1–1.011). A slightly linear decreasing trend in SCL mean was found after 10 months post-LTx; a significant 2% per month (95% CI: -0.03 to -0.019). CONCLUSION: AR history was found to be a risk factor in mortality in Iranian LTx recipients. Given the association between the higher SCL and lower mortality found in this study, it is recommended to pay serious attention to SCL changes in the overall post-transplantation survival assessment in Iranian LTx recipients.